2019
DOI: 10.7759/cureus.5692
|View full text |Cite
|
Sign up to set email alerts
|

Initial Treatment for Unruptured Intracranial Aneurysm and Its Follow-up: A Cost Analysis of Pipeline Flow Diverters versus Coiling

Abstract: PurposeIntracranial aneurysms are relatively common epidemiological problems for which the surveillance, treatment, and follow-up are costly. Although multiple studies have evaluated the treatment cost of aneurysms, the follow-up costs are often not examined. In our study, we analyzed how follow-up costs after treatment affected the overall cost of different endovascular techniques for treating aneurysms.Materials and methodsAn institutional database was used to evaluate the upfront and follow-up costs incurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Disease Markers embolization in the treatment of intracranial aneurysms in a meta-analysis. It has been reported that follow-up and upfront costs are close in treating aneurysms using coiling and flow diversion [17]. Equipment applications and quantities compose most entire costs in aneurysm treatments, but notable variations are depending on patient discharge disposition, rupture sta-tus, and surgical approach [18].…”
Section: Discussionmentioning
confidence: 99%
“…Disease Markers embolization in the treatment of intracranial aneurysms in a meta-analysis. It has been reported that follow-up and upfront costs are close in treating aneurysms using coiling and flow diversion [17]. Equipment applications and quantities compose most entire costs in aneurysm treatments, but notable variations are depending on patient discharge disposition, rupture sta-tus, and surgical approach [18].…”
Section: Discussionmentioning
confidence: 99%